Trust, trust repair, and public health: a scoping review - Kalulu, Peter; Fisher, Aubrey; Whitter, Grace; Sener, Ipek; Doering, Michelle; Carter, David B.; Gabel, Matthew; Ding, Jimin; Esposito, Michael; McMurtry, Caitlin L.; Sopory, Pradeep; Huffman, Mark D. (Frontiers in Public Health, 2025)
ObjectiveThis study investigates the scope of evidence on trust, trust repair, and public health.MethodsWe identified quantitative studies that evaluated the relationship between trust or trust repair and public health from January 1990 to May 2023. Results were stratified evaluating trust as an exposure or outcome and reporting on trust repair. Data are reported on spatiotemporal trends in publications, level of trust (institutional trust, generalized trust, and interpersonal trust), types of trust measures used, objects and determinants of trust, and associations between trust and public health behaviors.ResultsAmong 194 included studies, most (86%, 166/194) were published after the COVID-19 pandemic and in high-income countries. Among 40 reports that evaluated trust as an outcome, most (52%) evaluated trust in government. Socioeconomic factors (n = 18), perceived government performance (n = 14), and media/information (n = 8) were the most common determinants overall and for institutional trust. Three reports focused on trust repair (n = 2) or maintenance (n = 1).ConclusionThis review provides a roadmap for future research on evaluating and improving trust and public health.